PHYTOCHEMICAL AND ANTIMICROBIAL STUDIES OF STEM-BARK EXTRACTS OF ANOGEISSUSLEIOCARPUS FOUND IN DUTSIN-MA, KATSINA - NIGERIA - Usman, Abdulrasheed Halliru; Ali, T.; Danjani, A. G. (FUDMA JOURNAL OF SCIENCES, 2020)
Preliminary characterization of phytocompounds from stem bark of Anogeissusleiocarpus and its antimicrobial effects was carried out in this study. Concentrated and dried extracts obtained, after extraction of the plant material, were subjected to phytochemical screening and FT-IR analysis. Part of extracts obtained were used for antimicrobial studies on eleven pathogenic clinical isolates namely Methicillin resistant Staphylococcusaureus, Vancomycin resistant enterococci, Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Salmonella typhi, Candida krusei, Candida albicans and Candida stellatoidea using standard protocols. Phytochemical screening of the plant extracts revealed the presence of, alkaloids, steroids, saponins, tannins, flavonoids and reducing sugars. FT-IR’s spectroscopic analysis showed characteristic peaks of alcohols, ethers, esters, carboxylic acids, aldehydes, ketones and amines groups matching with some of the metabolitesâ€™ functionalities already reported in literature. The plant extracts were active against all the test organisms (MIC ranged from 5.0 mg / ml to 1.25 mg / ml; MBC/MFC ranged from 10 mg / ml to 2.5 mg / ml) except Methicillin resistant Staphylococcusaureus, Staphylococcus aureus, Klebsiella pneumonia and Candida krusei. It can be concluded that the stem-bark of Anogeissusleiocarpus contains phytochemicals that have potentials to be developed into antimicrobial drugs useful for the treatment of diseases caused by those microorganisms the plant indicated activity against it.